The use of technology in relationship management - Christelle Swart; Sonja Verwey (Communicare)
Technological innovations have changed many aspects of public relations practice, and public relations is believed to have entered the “fourth wave” of technological change in the field. To achieve its ultimate objective, namely to build and maintain beneficial relationships, thus contributing to achieving organisational goals, it is pivotal to explore the impact of technology on the profession and practice of public relations. Knowledge of the impact of these innovations will equip public relations with the required knowhow to contribute to the overall objectives of an integrated communication approach. While technology in itself cannot build or destroy relationships as maintained by Kent & Taylor (1998:324), the way in which technology is used can influence organisationpublic relationships, hence emphasising the need for public relations professionals to come to terms with new technology and the opportunities and challenges it holds. An exploratory study was undertaken to provide new insights into the impact of new communication technology on the profession and practice of public relations in South Africa. The primary purpose of the study was to determine the availability and use of new communication technology by South African public relations professionals for internal and external relationship management. It comprised a theoretical and conceptual analysis of public relations practice and models, dominant business approaches and other concepts related to the objectives of this study. The literature study was supplemented by a pilot study concerning the availability and use of technology by PRISA-accredited public relations practitioners. This article reports on the findings of the empirical section of the study